2018
DOI: 10.1186/s12879-018-3574-y
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes and factors affecting treatment outcomes of new patients with tuberculosis in Busan, South Korea: a retrospective study of a citywide registry, 2014–2015

Abstract: BackgroundThis study investigated the treatment outcomes, and factors affecting the outcomes, of new tuberculosis (TB) patients in Busan, South Korea.MethodsWe retrospectively analysed the citywide TB registry data (collected for the Korean National TB Surveillance System) of new TB patients registered in Busan from January 2014 to December 2015.ResultsA total of 4732 patients were included in this study (mean age, 52.5 ± 19.9 years; 58.4% male). The overall treatment success rate was 83.9% (cured, 20.2%; comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
20
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 25 publications
8
20
2
1
Order By: Relevance
“…Low treatment adherence in the elderly may be due to the higher risk of multi-morbidity and subsequent polypharmacy risk among this population, which may lead to a non-adherence to drugs compared to the younger population ( Roy et al, 2017 ; Freire et al, 2019 ). In the registry-based studies in South Korea and Spain, the adherences were also similar to our main result (South Korea, 63.7%; Spain, 69.1%) ( Ambrona de Marcos et al, 2018 ; Mok et al, 2018 ). However, given the inherent limitations of DOT trials or registry data, the association between medical use and adherence could not be assessed in previous studies.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Low treatment adherence in the elderly may be due to the higher risk of multi-morbidity and subsequent polypharmacy risk among this population, which may lead to a non-adherence to drugs compared to the younger population ( Roy et al, 2017 ; Freire et al, 2019 ). In the registry-based studies in South Korea and Spain, the adherences were also similar to our main result (South Korea, 63.7%; Spain, 69.1%) ( Ambrona de Marcos et al, 2018 ; Mok et al, 2018 ). However, given the inherent limitations of DOT trials or registry data, the association between medical use and adherence could not be assessed in previous studies.…”
Section: Discussionsupporting
confidence: 88%
“…Although several factors such as socioeconomic factors, regimen complexity, long duration of treatment, and pattern of health care delivery system are known to affect adherence to TB drugs, the extent to which additional factor affects TB adherence needs to be explored ( WHO, 2003 ). Past studies evaluating the adherence either focused on highly specific patient population, for instance, those with acquired immune deficiency syndrome ( Shayo et al, 2015 ; Dhungana et al, 2019 ), or based on local registry data with limited sample size and lack of medical history of the individual patient ( Mok et al, 2018 ). Therefore, we sought to assess the adherence to TB drugs and factors affecting adherence among TB patients in South Korea by using a nationwide claims database from 2017 to 2018.…”
Section: Introductionmentioning
confidence: 99%
“…For the citizenship factor, this study showed that non-citizen was significantly associated with unsuccessful treatment outcomes. The result of this study was similar to the one done in Busan [10]. Other local study showed that local citizen was at a higher risk for unsuccessful treatment outcome [5].…”
Section: Discussionsupporting
confidence: 87%
“…Many studies have shown similar to this study that old age is associated with unfavourable outcome in TB treatment [2, 19]. This finding could be attributed to an increased risk of lower immunity, making them more susceptible to infections, as a person grows older which may lead to poor outcomes [2, 20]. One important limitation is that secondary TB register data was used for this study, so we could not control for the age-associated co-morbidities.…”
Section: Discussionsupporting
confidence: 77%